Analysis of the therapeutic efficacy of OLIF combined with posterior percutaneous pedicle screw fixation in the treatment of patients with primary lumbar spondylodiscitis - Deng, Liang; Zhou, Yu; Xiong, Moliang; Zeng, Jihuan; Luo, Caiguang; Guo, Jia; Xiao, Qiang (Frontiers in Surgery, 2025)
IntroductionPrimary lumbar spondylodiscitis is a serious condition with an increasing incidence rate.MethodsFrom January 2021 to June 2023, we adopted a single-stage oblique lateral approach for the debridement of lumbar infection foci, intervertebral bone grafting fusion, tube irrigation drainage, combined with posterior percutaneous pedicle screw fixation for the treatment of primary lumbar spondylodiscitis.ResultsWe found that this surgical technique significantly improved the patients' lower back pain symptoms. During postoperative follow-ups at 1, 3, 6, and 12 months, patients showed remarkable improvements in their JOA and VAS scores, as well as in ESR and CRP levels, compared to the preoperative period.DiscussionWe believe that the single-stage oblique lateral approach for debridement of lumbar infection foci, intervertebral bone grafting fusion, tube irrigation drainage, and combined posterior percutaneous pedicle screw fixation is an ideal treatment method for primary lumbar spondylodiscitis. This technique offers thorough debridement of the infection focus, sufficient bone grafting, safe operation, and reliable fixation.